2020
DOI: 10.1080/00222895.2020.1748861
|View full text |Cite
|
Sign up to set email alerts
|

Topographical Working Memory in Children with Cerebral Palsy

Abstract: Forty children with cerebral palsy (CP) and 120 typical developing children (TD) performed a topographic working memory (WalCT) test requiring to move their body in a walked vista-space and a visuo-spatial test (CBT) requiring just reaching movements. WalCT score was significantly higher in GMFCS II/III than in TD. CBT score was significantly lower in GMFCS I than in III/IV but lower than TD in all CP groups. Similar results in WalCT between GMFCS I and TD and GMFCS II and III/IV respectively indicate that mob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
(57 reference statements)
0
7
0
Order By: Relevance
“…The methods of both WM tests have been thoroughly described in previous articles [ 1 , 2 ]. The CBT consists of nine blocks fixed on a baseboard (30 × 25 cm) which are numbered on the examiner’s side ( Figure 1 a).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods of both WM tests have been thoroughly described in previous articles [ 1 , 2 ]. The CBT consists of nine blocks fixed on a baseboard (30 × 25 cm) which are numbered on the examiner’s side ( Figure 1 a).…”
Section: Methodsmentioning
confidence: 99%
“…In studies of topographic working memory (TWM), comparing typical developing children (TD) with children with motor disabilities, difficulties were associated with perceptual-motor conditions in some children, whereas no influence of age was reported in any patient group [ 1 , 2 ]. The present study focuses on the influence of age on working memory (WM) in navigational and reaching spaces in a group of TD.…”
Section: Introductionmentioning
confidence: 99%
“…DTD. In this vein, Bartonek and co-workers [88][89][90] showed that children with cerebral palsy and motor disability manifested differences in topographic working memory as a function of the degree of autonomy to explore the environment, regardless of motor impairment. Our results also showed that the use of advanced navigational strategies (survey strategies) is not associated with the presence of DTD.…”
Section: Plos Onementioning
confidence: 99%
“…Spatial memory locomotor neuropsychological assessment (SMLNP) Numerous SMLNPs paradigms have been developed [18] and applied in a variety of studies, ranging from establishing the relationship between critical components of human navigation, such as spatial representation, goaldirected navigation, learning, and spatial performance enhancement [19] to determining what, how, and which part of the brain contributes to navigational information processing [20].…”
Section: 1mentioning
confidence: 99%